Phase Locking to High Frequencies in the Auditory Nerve and Cochlear Nucleus Magnocellularis of the Barn Owl, Tyto alba - Köppl, Christine (J Neurosci, 1997)
The auditory system of the barn owl is an important model for temporal processing on a very fast time scale and for the neural mechanisms and circuitry underlying sound localization. Phase locking has been shown to be the behaviorally relevant temporal code. This study examined the quality and intensity dependence of phase locking in single auditory nerve fibers of the barn owl to define the input to the known brainstem circuit for temporal processing. For direct comparison in the same individuals, recordings were also obtained from the relevant next higher center, the nucleus magnocellularis (NM). Phase locking was regularly seen at sound pressure levels (SPL) below those eliciting an increase in spike rate, thus providing an additional cue for signal detection. The quality of phase locking, expressed as vector strength, decreased with increasing frequency. Auditory nerve fibers showed an unusual step-like decline with a prominent plateau in the mid-frequency range (1.5–3 kHz), indicating that some specialization enables the owl to halt the deterioration and extend phase locking to frequencies up to 10 kHz, above the range commonly observed in other species. Phase locking in the NM was consistently inferior to that of auditory-nerve fibers at frequencies above 1 kHz, suggesting that the synapse plays a limiting role in temporal precision. The response delays, or group delays, derived from the phase-versus-frequency functions of auditory nerve fibers were not consistent with the unusual spatial frequency representation in the owl cochlea. This questions the common assumption that group delays reflect cochlear wave travel times.